Ghana : Sector Reform and the Pattern of the Poor - Edjekumhene, Ishmael; Amaka-Otchere, Akosua B.K.; Amissah-Arthur, Harriette (World Bank, Washington, DC, 2014)
The overarching goal of this study, which forms part of the broader project 'Energy Use, Energy Supply, Sector Reform and the Poor', is to establish patterns in the ways poor people in Ghana are accessing and using energy and to identify how changes in the patterns, attributable to energy sector reform and accompanying technological innovations, affect the Ghanaian poor. The study will seek to achieve the following: (i) give an overview of the Ghana's energy sector; (ii) provide a description of the energy supply chain in Ghana; (iii) provide a description of household choice and use of energy in Ghana; (iv) provide a description of Ghana's energy sector reform program and give an assessment of how reform has impacted on the poor in Ghana; and (v) evaluate how energy sector reform has impacted or might impact on the choice and use of energy by the poor in Ghana.